P23 Adult onset Still's disease as a novel autoimmune complication of alemtuzumab therapy: a case report and review of alemtuzumab associated autoimmune disease. (20th April 2020) - Narayan, Nehal; Mazibrada, Gordon; Amft, Nicole
Abstract: Background: Alemtuzumab is a monoclonal antibody targeted to CD52, an antigen of uncertain function on T and B lymphocytes. Alemtuzumab is an established treatment for active relapsing and remitting multiple sclerosis (MS). However, autoimmune disease (AID) is being increasingly recognised as a highly prevalent adverse effect of alemtuzumab treatment. Methods: We describe a case of adult onset Still's disease (AOSD) developing in a patient six months after alemtuzumab therapy, highlighting the need for awareness of the risk of AID in those who develop symptoms after alemtuzumab treatment, some of which can be potentially life-threatening. Results: Our patient, a 37 year old female, was admitted to hospital with a three week history of fevers up to 39ºC, a flitting macular rash, sore throat and polyarthritis, neutrophils 35.2x10 9 /L (2-7.5), ferritin 8349 ug/L (normal 15-150), ALP 151 U/L (25-105). She had a history of relapsing and remitting multiple sclerosis, that went into remission after treatment with alemtuzumab six months previously. Despite 72 hours of broad-spectrum intravenous antibiotics, fever and symptoms were unchanged. Immunology and microbiology tests were negative. CT scan of neck, chest abdomen and pelvis were unremarkable. A diagnosis of AOSD was made. She received prednisolone at 40mg daily and symptoms rapidly settled. By day three of prednisolone, ferritin had fallen to 3238, neutrophil count had halved, and ALP normalised. She continues on slow weaning of steroids and remains asymptomatic. Conclusion: Alemtuzumab was approved in 2013 as a treatment for active relapsing and remitting MS. Treatment consists of two courses of 'induction' treatment 12 months apart, aiming to deplete T and B lymphocytes, with subsequent lymphocyte repopulation. Without requirement for continued 'maintainance' treatment, efficacy of alemtuzumab persists for years. The most common alemtuzumab associated AID are thyroid disease, nephropathies and immune thrombocytopenia. However, other AID has been reported, including sarcoidosis. To date, no reports exist describing AOSD post alemtuzumab therapy. Although lymphocyte reconstitution post alemtuzumab is thought to account for its therapeutic effects, this same reconstitution is postulated to contribute to AID. Baker et. al. postulated that rapid re-population of B lymphocytes and slower re-population of regulatory T lymphocytes may trigger B cell mediated AID. Further, rapid repopulation of immature B cells post alemtuzumab is associated with raised serum B cell activating factor (BAFF), which remains elevated for at least a year post treatment. BAFF has been recognised in multiple animal studies to be associated with antibody mediated AID. The hypothesis that B cells play a key role in alemtuzumab related AID may be supported by the success of rituximab in treating 2 cases of alemtuzumab associated AID. The possible critical role of B cells in the pathogenesis of alemtuzumab related AID could indicate a future treatment strategy for such AID. Disclosures: N. Narayan None. G. Mazibrada None. N. Amft None.